Environmental determinants of type 1 diabetes: A role for overweight and insulin resistance. (3rd June 2014) - Islam, Sadia T; Srinivasan, Shubha; Craig, Maria E
Abstract Rates of type 1 diabetes are rising globally, with a decreasing proportion of high‐risk genotypes and twin concordance rates below 50%. Therefore, environmental factors such as viruses, nutrition and overweight have been examined as putative aetiological agents. The accelerator hypothesis proposes that overweight and insulin resistance are central to both type 1 and type 2 diabetes and may explain, in part, the rise in type 1 diabetes incidence. The temporal rise in body mass index at type 1 diabetes onset and the observation that pre‐diabetic children are heavier and more insulin resistant than their peers suggests convergence of type 1 and type 2 diabetes phenotypes. The influence of insulin resistance may begin in utero, although the aetiological role of birthweight in type 1 diabetes remains unclear. Further research to elucidate the role of these modifiable risk factors in today's obesogenic environment may provide future potential for diabetes prevention.